(untitled) (Bangladesh Journal of Plant Taxonomy, 2013)
Ranunculus shanyangensis M.R. Luo & L. Zhao, a new species of Ranunculaceae from Shaanxi, China, is described and illustrated. Ranunculus shanyangensis is morphologically similar to R. repens, however, it differs from the latter due to the following characters: longer adventitious roots, wholly creeping stems with no branches, longer rachis, fewer floral organs and pollen wall sculpturing. SEM micrography of thepollens for R. shanyangensis and R. repens are presented along with distribution map. DOI: http://dx.doi.org/10.3329/bjpt.v20i2.17394 Bangladesh J. Plant Taxon. 20(2): 201-205, 2013